PREDNISOLONE ENCAPSULATED SUPERPARAMAGNETIC IRON OXIDE NANOPARTICLES FOR TARGET DRUG DELIVERY – DESIGN AND QUANTIFICATION - SUBASHINI RAJARAM; SENTHIL RAJAN DHARMALINGAM; SANTHOSE RANI A; SAPTHASRI R; VARSHA D; VINODHINI V (Asian Journal of Pharmaceutical and Clinical Research, 2019)
Objective: The present study aimed to develop a novel type of superparamagnetic iron oxide nanoparticles (SPIONs) to deliver prednisolone at colon as a target site for the treatment of inflammatory bowel disease (IBD) such as ulcerative colitis and Crohn’s disease which may further progress to cancer. Methods: SPIONs were synthesized using a coprecipitation method. Further, it was encapsulated with prednisolone-polyethylene glycol by double emulsion method (W1/O/W2). The prepared formulations were characterized for its physicochemical characterization such as scanning electron microscopy, X-ray diffraction, particle size and zeta potential, encapsulation efficiency, and in vitro drug release. Results: The results reveal that the physicochemical property of the formulations complies with the standard values and in vitro release of prednisolone in the first 18 h, attains 57 and 58% and it reaches 71 and 75% at 24 h, and this is statistically significant (p˂0.0177). This release result implies that the drug release from the formulations is controllable and sustains manner. Conclusion: Our findings could be a promising approach for the delivery of prednisolone with enhanced half-life for the treatment of IBD through colon targeting.